PERANCANGAN KONSEP AERODROME MAPPING MENGGUNAKAN SOFTWARE QGIS DI BANDAR UDARA INTERNASIONAL SOEKARNO HATTA - Alifah, Sadanah (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The transition from Aeronautical Information Services (AIS) to Aeronautical Information Management (AIM) requires the availability of digital and interoperable aeronautical data, including Aerodrome Mapping Data Sets (AMDS). However, available data shows that AMDS is not yet available in Indonesia. This study aims to design an aerodrome mapping concept using QGIS software at Soekarno Hatta International Airport, utilizing satellite imagery as secondary data as an initial step in developing AMDS in Indonesia. This research uses the Research and Development (R&D) Level 1 method. It begins with a preliminary study and data collection through literature review, satellite image analysis, and interviews. The concept design process uses QGIS Desktop 3.26 and PostgreSQL software, referencing ICAO Doc 10066 Appendix 1 (AIM Data Catalogue) and Airnav Indonesia DQR. This concept design also integrates visualization of aerodrome operational conditions based on NOTAM using rule-based symbology. The design was validated through interviews with GIS Specialists, AIS personnel and the Assistant VP of AIM Planning at Airnav Indonesia to ensure its suitability and feasibility. The research resulted in the creation of an aerodrome mapping concept design that is suitable and feasible for further development. Although it uses secondary data, this concept design provides an important initial overview for the implementation of AMDS in Indonesia.